2001
DOI: 10.1002/1531-8257(200101)16:1<114::aid-mds1004>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Re-emergence of childhood stuttering in Parkinson's disease: A hypothesis

Abstract: OBJECTIVE To characterize speech patterns in patients with Parkinson's disease (PD) who have a history of childhood stuttering. BACKGROUND Childhood stuttering usually resolves, but it re‐emerges in some patients after stroke or other brain disorders. This phenomenon of recurrent stuttering has not been characterized in childhood stutterers who later develop PD. METHODS/PATIENTS Twelve patients with a history of childhood stuttering that remitted and subsequently recurred were included in the study. A structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Yet, not the actual dose, but only the cumulative dopaminergic dose over the whole period of dopaminergic treatment correlated with the severity of dysfluency, this may reflect more complex factors related to individual severity of PD symptoms, need of therapy and response to treatment. Notably, in their seminal observation of recurrent childhood stuttering in patients with PD, Shahed and Jankovic noted that patients with higher UPDRS motor scores tended to have more and worse symptoms of stuttering (Shahed and Jankovic 2001). From a different perspective, in PD patients without history of childhood stuttering, a significant negative correlation has been found between self-ratings of medication effectiveness and dysfluency levels (Goberman et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, not the actual dose, but only the cumulative dopaminergic dose over the whole period of dopaminergic treatment correlated with the severity of dysfluency, this may reflect more complex factors related to individual severity of PD symptoms, need of therapy and response to treatment. Notably, in their seminal observation of recurrent childhood stuttering in patients with PD, Shahed and Jankovic noted that patients with higher UPDRS motor scores tended to have more and worse symptoms of stuttering (Shahed and Jankovic 2001). From a different perspective, in PD patients without history of childhood stuttering, a significant negative correlation has been found between self-ratings of medication effectiveness and dysfluency levels (Goberman et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a group of 53 patients in moderate and advanced stages of PD, acquired speech dysfluencies were pronounced in 15 patients (28 %), 13 of whom belonged to the advanced disease group (Benke et al 2000). Furthermore, Shahed and Jankovic (2001) reported 12 PD patients with a history of developmental stuttering who remitted and subsequently re-emerged stuttering on average 6 years after the onset of PD symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Within-word disfluencies may also be viewed as more motoric-based compared to between-word disfluencies, and between-word disfluencies may be influenced by language factors such as slow word retrieval or poor semantic and syntactic planning. Previous studies have also found motoric-based disfluencies in parkinsonian speech (Goberman & Blomgren, 2003;Shahed & Jankovic, 2001). Further, in Canter's (1971) description of neurogenic stuttering, he described neurogenic stuttering as dysarthric (based on faulty motor execution), apraxic (based on cerebral motor programming problems), or dysnomic (based on language -word retrieval problems).…”
Section: Disfluencies In Pdmentioning
confidence: 96%
“…Notably, the first patient had a recurrence of speech dysfluencies, since he had suffered from developmental stuttering. The recurrence of stuttering has already been reported in cases of Parkinson's disease (Shahed & Jankovic, 2001) which might suggest a common underlying mechanism for dysfluencies in acquired and developmental stuttering.…”
Section: Resultsmentioning
confidence: 79%